Macropropagation in Banana (Musa spp.): Varietal Response to Media and Field Performance of Plantlets Against Suckers - Manju, P. R.; Pushpalatha, P.B. (International Journal of Bio-resource and Stress Management, 2022)
The experiment was conducted during December 2020 to March 2022 at Banana Research Station, Kannara, Kerala Agricultural University, Thrissur, Kerala, India to evaluate the response of different banana varieties Nendran, Kadali, Rasthali, Neypoovan, Poovan (Palayankodan) and Grand Naine to macropropagation with two different media (sawdust and cocopeat) and to assess the performance of plantlets generated against suckers. The plantain variety nendran took the shortest time for primary (20.33 days) and secondary bud regeneration (14.33 days) with sawdust as media. Total duration from planting to hardening ranged from 75.9 days in Nendran (sawdust media) to 104.3 days in Poovan (cocopeat media). Significantly shorter duration was observed with saw dust in Nendran, Kadali, Rasthali and Grand Naine compared to cocopeat. The cost of production varied with the variety which ranged from Rs. 1.7−4.0 plantlet-1 in sawdust to Rs. 3.2−6.3 plantlet-1 in cocopeat. Macropropagated plantlets recorded higher bunch weight than suckers in all varieties. There was no significant difference between the 2 with respect to growth characters like plant height, pseudostem girth, suckers plant-1, days to bunching, days to maturity and crop duration across all varieties except for Neypoovan and Poovan. Quality characters like TSS and fruit acidity did not vary between the two planting materials.